Pembinaan Kasus Bullying Oleh Guru Bimbingan Konseling Terhadap Siswa SMPN 2 Mojoagung Jombang - Moh. Irfan; Shofwatal Qolbiyyah; Uswatun Hasanah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This research ains to explore how Guidance and Counseling teachers address bullying cases involving both perpetrators and victims at SMPN 2 Mojoagung Jombang.The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that bullying at SMPN 2 Mojoagung Jombang manifests in both physical and psychological forms, typically occurring when students with perceived weaker. The causes of bullying are influenced by internal and external factors. Internal factors include personality traits and family attitudes that hinder the development of mature character, while external factors relate to environmental and cultural conditions. To address these issues, Guidance and Counseling teachers provide continuous support through individual counseling, information sessions, and character-building activies, both inside and outside the classroom, thereby reducing bullying incidents. Additionally, the 5S program ( smile, greet, handshake, polite address, and courtesy ) is promoted, Regular evaluations are conducted to assess the effectiveness of these interventions, particularly in relation to bullying prevention. Keywords: Bullying, Guidance and Counseling, Students